Positive academic leadership how to stop putting out fires and begin making a difference - Buller, Jeffrey L. (Jossey-Bass higher and adult education series., 2013)
In Positive Academic Leadership, Jeffrey Buller offers new insights and practical tools, as well as language and tactics, for fostering a more effective approach to leadership. With acumen and a dash of humor, he shows leaders how they can take the focus off the negative and change what they say, their perspectives, and their strategies. This more constructive leadership style plays to the strengths of leaders rather than to the weaknesses of their institutions. Offering time-tested and fresh ideas for becoming the type of leader who acts as a coach, counselor, and conductor for faculty, staff, and students, Buller demonstrates how positive leadership can become a day-to-day practice. With its down-to-earth style, the book draws on the most current research on positive leadership in neuroscience, psychology, management, organizational behavior, and other disciplines and translates their lessons into readable and accessible recommendations. It then makes these recommendations come to life by providing real-world examples that illustrate how to implement positive leadership strategies in all spheres of the leader's activities and institution. Positive Academic Leadership is a wise guide for transforming any leader's attitude about inevitable daily crises into manageable challenges that are based on a philosophy of accepting the environment and situation but working to make things better.